Caregiver expectations of recovery among persons with spinal cord injury at three and six months post-injury: A brief report. (2nd January 2020) - Agtarap, Stephanie; Carl, Emily; Reynolds, Megan C.; Roden-Foreman, Kenleigh; Bennett, Monica; Rainey, Evan; Powers, Mark B.; Driver, Simon; Warren, Ann Marie
Abstract : Objective: Caregivers of patients with spinal cord injury (SCI) have increased risk of depression, anxiety, and diminished quality of life. Unmet expectations for recovery may contribute to poorer outcomes. Design: Prospective, longitudinal observation study. Settings: Trauma/Critical care ICU at baseline, telephone for follow-ups. Participants : Caregivers of patients with SCI ( n = 13). Interventions: None. Outcome Measures: Expectations for recovery were assessed across four primary domains identified in a review of the literature including: pain severity, level of engagement in social/recreational activities, sleep quality, and ability to return to work/school. Caregivers' forecasts of future recovery were compared to later perceived actual recovery. Results: At three months, 75% of caregivers had unmet expectations for social engagement recovery, 50% had unmet expectations for pain decrease, and 42% had unmet expectations for sleep improvement and resuming work. Rates of unmet expectations were similar at six months, with 70% of caregivers reporting unmet expectations for social engagement recovery, 50% with unmet expectations for pain decrease, and 40% with unmet expectations for sleep improvement. Conclusion: Unmet caregiver expectations for recovery could pose a risk for caregiver recovery and adjustment. Our results show that caregiver expectations merit further investigation for their link with caregiver mental health.